IPSec VPN design - Bollapragada, Vijay (Cisco Press, 2005)
This security book is part of the Cisco Press® Networking Technology Series. Security titles from Cisco Press help networking professionals secure critical data and resources, prevent and mitigate network attacks, and build end-to-end self-defending networks.